Cationic starch as a dry strength agent in magnetic papermaking - Ainun Zuriyati Mohamed @ Asa’ari; Sarani Zakaria; Roslinda Shamsudin; Mustaffa Abdullah (Universiti Kebangsaan Malaysia, 2010)
The mechanical strength of magnetic lumen loaded handsheets was reported to be lower than the unloaded handsheets. This effect is due to the deposition of filler inside the fiber lumen and some on the fibre surface which interfere with the fibre to fibre bonding. Hence, in order to improve the handsheets strength, cationic starch is used as a dry strength additive. In this study, mixed tropical hardwood pulps were used throughout the experiment. The magnetite particles were deposited in the fibre lumen via the lumen loading technique. The addition of cationic starch was found to increase the handsheet strength. However, it disturbed and influenced the location and distribution of the magnetic fillers. Some of the magnetite particles were observed to be displaced from the fiber lumen and pit apertures. The charges of the filler particles and cationic starch played an important role in producing charge repulsion and pulling effect which lead to filler dislocation.